FAKTOR- FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN POCKET DOSEMETER PADA PETUGAS RADIOLOGI DI INSTALASI RADIOLOGI 9 RUMAH SAKIT BANDAR LAMPUNG - Anggraeni, Leny (JURNAL TERAS KESEHATAN, 2020)
Radiation protection equipment Thermoluminisence Dosemeter (TLD) Badge can reduce and protect Radiology Officers. The purpose of this study was to determine the factors associated with the use of pocket dosemeter in the danger of radiation to the health and safety of officers with different levels of ease. Quantitative Research Design with Crossectional, the number of respondents 59 people. Primary data consisted of questionnaires, research questionnaires consisting of the characteristics of respondents, level of knowledge, attitude, approval of tools, comfort, training, supervision. Data analysis uses Univariate analysis which is visualized in tabular form. This analysis is done by calculating the distribution and percentage of each variable, while the bivariate analysis uses the chi  square test and multivariate analysis using logistic regression. The results showed the knowledge variable p value = 0, 018. Attitude p value = 0, 038. The value of the tool p value = 0, 004.